Comparative performance of the human papillomavirus test and cytology for primary screening for high‐grade cervical intraepithelial neoplasia at the population level. Issue 9 (29th December 2021) - Hurtado‐Salgado, Erika; Cárdenas‐Cárdenas, Luz; Salmerón, Jorge; Luna‐Gordillo, Rufino; Ortiz‐Panozo, Eduardo; Allen‐Leigh, Betania; Saavedra‐Lara, Nenetzen; Franco, Eduardo L.; Lazcano‐Ponce, Eduardo
Abstract: The World Health Organization recommends high‐risk human papillomavirus (hrHPV)‐based screening for women 39 to 49 years, based on the greater accuracy of hrHPV‐based screening for cervical cancer detection. Many cervical cancer screening programs have incorporated hrHPV testing and multiple early cervical cancer detection strategies have been evaluated, mostly under controlled conditions. However, there are few evaluations of combined hrHPV and cytology strategies post‐implementation at the population level. Our study sought to estimate the relative yield of hrHPV testing compared to cervical cytology, as a primary screening test for cervical intraepithelial neoplasia grade 2+ (CIN2+), used at the population level. We analyzed screening data from Mexico's public cervical cancer prevention program from 2010 to 2015 in women 35 to 64 years. The study population consisted of two cohorts: one from a total of 2 881 962 cytology‐based screening tests and another from a total of 2 004 497 hrHPV‐based screening tests, which are concurrent in time. We performed a relative yield analysis using Poisson regression models to compare the effectiveness of hrHPV testing for CIN2+ with cervical cytology. A total of 4 886 459 records were analyzed, including 23 999 biopsies; 0.12% (n = 6166) had a CIN2+ histologic diagnosis. hrHPV testing with cytological triage detects twice as many CIN2+ cases as screening using cytology alone. Abstract : What's new? Many cervical cancer screening programmes have incorporated high‐risk human papillomavirus (hrHPV) testing. However, there are few evaluations of combined hrHPV and cytology strategies at the population level. Using data from 4, 886, 459 screening tests and biopsies from 23, 999 women 35–64 years of age over a 6‐year period, this study compared the performance of hrHPV screening with cytological triage to cytology alone for early detection of high‐grade cervical lesions. hrHPV screening with cytological triage detected twice as many CIN2+ cases as screening with cytology alone in the real‐life conditions of a cervical cancer screening programme in a large middle‐income country.